Japan’s Advocacy for Human Security in Global Politics: Case Study of Japan’s Grant Assistance for Grass-Roots Human Security Projects (GGP) in the State of Sabah, Malaysia, 2000–2021 - Ramli Dollah; Diana Peters; Wan Shawaluddin Wan Hassan; Marja Azlima Omar; Md Safe Abdul Rahim; Adi Jafar (Springer Nature B.V., 2023)
After World War II, Japan became a major recipient of foreign aid from the USA. As Japan’s economy improved in the 1960s, it played a significant role as a global aid donor in world politics through its Official Development Assistance (ODA). This commitment continued into the 1990s when Japan, as one of the leading proponents of the concept of human security, began providing humanitarian aid to more countries across the globe. To better understand the notion of human security in international politics, this paper examines Japan’s endorsement of the concept in its foreign policy strategy. This paper provides an overview and critical assessment of Japan’s Grant Assistance for Grass-Roots Human Security Projects (GGP) in the state of Sabah in East Malaysia from 2000 to 2021. This paper argues that different contexts and circumstances in the state of Sabah require further study, especially for understanding Japan’s focus and concern in the area of basic human security needs, as enshrined in the GGP philosophy. Despite Japan’s GGP objective as part of its foreign policy to promote human development, the execution of its foreign aid in Sabah does have issues. This paper concludes that the implementation of Japan’s GGP necessitates greater inclusion, particularly for other vulnerable groups and underdeveloped areas in Sabah. Despite Japan’s GGP objective as part of its foreign policy to promote human development, the execution of its foreign aid in Sabah does have issues. This paper concludes that the implementation of Japan’s GGP necessitates greater inclusion, particularly for other vulnerable groups and underdeveloped areas in Sabah.